Effective parameter range for equivalence of velocity-level and acceleration-level redundancy resolution schemes - Zhang, Yunong; Wu, Huarong; Guo, Dongsheng; Xiao, Lin (Physics letters. A, 2012)
This Letter shows the equivalence of the velocity-level and acceleration-level redundancy resolution schemes by using so-called Zhang et al.ʼs neural-dynamic method. In addition, the equivalence requires that a design parameter be sufficiently large. But how large should it be? The effective range of such a design parameter is thus determined by means of the 2%-difference rule and the runtime of the computer-simulations. ► Equivalence of the two classes of redundancy resolution schemes is further proved. ► This Letter finds that the equivalence is closely related to a design parameter. ► Effective range for the design parameter is determined for the first time.